Using Open Source for forensic purposes - Delgado, M.; Aparicio, M.; Costa, C. (Workshop on Open Source and Design of Communication, OSDOC 2012, 2012)
This article provides an overview of thebasic digital forensic process. In different contexts of crime, the use of "computer forensics" is a usual way to gather evidence. Digital data is collected and analyzed in order to be presented in courtas evidenceof illegal activities. This is already afirst-line optionin mostcasesfor criminal investigation. For some types of crime,particularly economic and financial research focuses on thestorage devices.In the context of a crime,create and certify a full Image of suspect device sis vitalto preserveits integrity.The disk image, takesector by sector copy usually for forensic purposes, and as such will contain some mechanism(internal verification) to prove that the copy is accurate and has not changed.In this work we present some Open Source tools to perform an effective role in computer forensics, which ensure the realization of these images, fulfilling all the requirements, so that any evidence recovered from his analysis, may be admitted in court.